(untitled) (ENTHYMEMA, 2020)
The figure of the interpreter in history has always oscillated between visibility and invisibility. Although today there is a tendency to give it increasing recognition, some categories (cultural mediators, war and sign interpreters) still remain in a poorly recognized situation and often operate in precarious working conditions. The interpreter as a subject of study has been present in world literature for years. We will investigate what has become the interpreter as a subject in world cinema. What is the semiotic process for which a given image of the interpreter communicates a certain cliché or suggests certain characteristics that the director (or the screenwriter) wanted to highlight. Will the cinematographic fictional representation tend to distort, between myth and stereotype, the working reality of the interpreter? In which cases and why? These are some of the questions we will try to answer through our study based on a representative corpus of international films.